PENILAIAN RISIKO KECELAKAAN KERJA PADA BAGIAN PENGOLAHAN KELAPA SAWIT (PKS) DI PTPN IV KEBUN SOSA TAHUN 2015 - eva novia andani; halinda sari lubis; lina tarigan (Lingkungan dan Kesehatan Kerja, 2015)
Abstract Risk assessment of workplace accidents in the palm oil processing (MCC) in PTP N IV gardens Sosa 2015. This research is a descriptive that aims to find occupational risk of workplace accidents in the palm oil processing (MCC) in PTP N IV Sosa garden. The population in this study were all workers palm processing section (MCC) in PTP N IV gardens Sosa 2015 as many as 100 people, the samples in this study were 50 people. Results of this study shown in Table 4.1 can be seen that the average level of risk of workplace accidents in the fruit reception station at moderate risk level of risk with a score of 5-9, which means the risk of accidents can still be controlled up to the limit of tolerance. In Table 4.2 it can be seen that the level of risk at high risk of work accidents at boiling stations on the risk level of high risk with a score of 10-16, which means the risk of accidents conducted intensive monitoring and control. In Table 4.3 it can be seen that the average level of risk of workplace accidents in threser station at moderate risk level of risk with a score of 5-9, which means the risk of accidents can still be controlled up to the limit of tolerance. In Table 4.4 it can be seen that the average level of accident risk fruit reception station at moderate risk level of risk with a score of 5-9, which means the risk of accidents can still be controlled up to the limit of tolerance. In Table 4.5 it can be seen that the average level of accident risk kerjapada fruit reception station at moderate risk level of risk with a score of 5-9, which means the risk of accidents can still be controlled up to the limit of tolerance